Cardiovascular accident unveiling rheumatic heart disease - B. E., Pavithra Shree; K. B., Namratha; N., Pradeep (International Journal of Contemporary Pediatrics, 2022)
Infection with group A Streptococci causes an autoimmune reaction known as acute rheumatic fever (ARF) which leads to chronic cardiac condition called rheumatic heart disease (RHD). Rheumatic involvement of the cardiac valves is one of the sequelae of ARF. The valvular lesions begin as verrucae along the borders of heart valves and tend to resolve leaving a scar once the inflammation subsides. Cardio embolism is seen as the main pathophysiological mechanism of ischemic stroke in RHD.